How to be an explorer of the world : portable art life museum - Smith, Keri (Penguin, 2011)
Artists and scientists analyze the world around them in surprisingly similar ways, by observing, collecting, documenting, analyzing, and comparing. In this captivating guided journal, readers are encouraged to explore their world as both artists and scientists. The mission Smith proposes? To document and observe the world around you as if you've never seen it before. Take notes. Collect things you find on your travels. Document findings. Notice patterns. Copy. Trace. Focus on one thing at a time. Record what you are drawn to. Through this series of beautifully hand-illustrated interactive prompts, readers will enjoy exploring and discovering the world in ways they never even imagined.